Spatial distribution and influencing factors of rural cultural ecosystem services: a case study of Fujian, China - Congzhi Li; Ying Pan; Weilun Yin; Siren Lan (Scientific Reports)
Abstract Rural cultural ecosystem services (CES) play a pivotal role in enhancing rural well-being. This paper examines the spatial distribution patterns and influencing factors of rural CES in Fujian Province using the biterm topic model and geodetector. The results reveal that rural CES in Fujian Province comprise five categories: culture, leisure, aesthetic, spirit, and science, among which leisure, culture, and aesthetic categories are the most easily perceived by the public. In terms of spatial distribution, the northwestern regions of Fujian Province exhibit better than the southeastern regions in terms of culture, while the latter excel in terms of leisure. Regarding aesthetics, there is an overall trend of extensive dispersion with localized concentrations, with high-value areas primarily located in the southwestern region and the eastern coastal region of Ningde City. The high value areas in the spirit are concentrated in the central and northern regions of Fujian Province. The spatial distribution of science is relatively scattered, with more high-value areas observed in Sanming City and Fuzhou City. Road density, light index, and per capita disposable income demonstrate strong explanatory power in rural CES. These findings can guide targeted development of regional cultural services and address resource mismatches in rural areas of Fujian Province, thereby enhancing the well-being of rural residents.